1972
DOI: 10.1136/bmj.3.5829.724
|View full text |Cite
|
Sign up to set email alerts
|

Daily Requirement of Oxygen to Reverse Pulmonary Hypertension in Patients with Chronic Bronchitis

Abstract: SummaryWe have shown previously in patients with chronic bronchitis that correction of the hypoxaemia by continuous administration of oxygen substantially reduced the pulmonary hypertension by reversal of structural changes in the pulmonary resistance vessels. We have now demonstrated that such improvements may occur with less than continuous oxygen. Treatment with oxygen for 18 hours daily significantly decreased pulmonary arterial pressure and pulmonary vascular resistance. Oxygen therapy for 15 hours a day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…We attempted to answer three questions: (1 ) What effect does LVRS have on resting pulmonary hemodynamics as compared with medical therapy, (2 ) What is the relationship between changes in lung function to changes in pulmonary hemodynamics after LVRS, and (3 ) What is the relationship between hemodynamic changes after LVRS and the changes that occur during exercise testing?…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…We attempted to answer three questions: (1 ) What effect does LVRS have on resting pulmonary hemodynamics as compared with medical therapy, (2 ) What is the relationship between changes in lung function to changes in pulmonary hemodynamics after LVRS, and (3 ) What is the relationship between hemodynamic changes after LVRS and the changes that occur during exercise testing?…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…tion with decreased cross-sectional area of the pulmonary vasculature, may increase pulmonary vascular resistance (PVR) (2)(3)(4)(5). Hyperinflation may impair left (LV) or right ventricular (RV) diastolic filling (6)(7)(8)(9).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…Adequate oxygenation is achieved in the majority of subjects with a flow of [1][2][3] 14 patients.23 Moreover, in the NWRHA trial the frequency distribution of the number of hours per day that patients used their concentrators was negatively skewed; indeed six of the 76 patients were using their machines for less than six hours a day. Thus it appears that, if the necessary minimum daily duration of oxygen therapy for improved survival to accrue is in fact 15 hours,6 and the findings of the NWRHA study are representative of patient compliance in this country, then over half of the recipients will be having insufficient treatment.…”
Section: Indications For Long Term Oxygen Therapymentioning
confidence: 99%
“…For this purpose, according to the best available evidence, controlled oxygen supplements are required by the patient for a total of between 12 and 24 hours daily. [3][4][5][6][7][8] It is with such long term oxygen therapy (LTOT) that we are concerned here.…”
Section: Provision Of Long Term Oxygen Therapymentioning
confidence: 99%
“…Stark et al demonstrated in 1972 that as little as 12-15 hours of oxygen a day improved hemodynamics as effectively as 24 hours of oxygen use. 22 These findings created the ethical equipoise to propose multicenter trials to test the effects of duration of oxygen therapy on patient outcomes.…”
Section: Early Scientific Evidence Of Oxygenmentioning
confidence: 99%